A History of Disciplines and Curriculum as the Grounds for Writing the History of Highschool Teaching in Brazil - Eurize Caldas Pessanha (Universidad Pedagógica Nacional, 2016)
This article falls into History of Education and focuses the history of school in its singularity, features, inner relations and practices. Some researchers have undertaken the task to write the history of curriculum practices in secondary education schools in Brazil. They have turned to many resources, being the richest ones nation and department laws that make up the prescribed curriculum, supplemented by the discussions that triggered, caused or altered them. Their analyses state that, for long decades, curriculum prescriptions and practices provided in that teaching level marked the tension between two proposals of schoolwork organization and curriculum, a humanist proposal versus a scientitic proposal.